THE DIFFERENCE OF HUSBAND’S KNOWLEDGE ABOUT EXCLUSIVE BREASTFEEDING AND THEIR SUPPORT AMONG WOMEN WHO FEED THEIR BABIES WITH EXCLUSIVE BREASTFEEDING AND THOSE WHO DO NOT ON PANDANWANGI LOCAL GOVERNMENT CLINIC REGION BLIMBING MALANG - Yuliatun, Laily; Laily, Maghfiratul (University of Muhammadiyah Malang, 2012)
The success of exclusive breastfeeding supplies influenced by internal and external factors. Father?s knowledge level about exclusive breastfeeding and father?s support for breastfeeding mother are include in external factor. This research intends to prove that there is a difference of husband?s knowledge about exclusive breastfeeding and their support among women who feed their babies with exclusive breastfeeding and those who do not. This research is a crossectional study with population of this research is married couples who have baby ages 6-7 months. The number of sample in this research is 38 respondents chosen with purposive sampling technique. Research data is collected by questionnaire with close ended question type, and then analized with mann whitney test. The result of this research showed that 81% respondents have good knowledge level about exclusive breastfeeding and 45% respondents are adequatly support mother to breastfeed. Result of knowledge level produces a significance by p = 0,037 (p < 0,05), whereas for father?s support produces a significance by p = 0,001 (p < 0,05). From both of sinificance value, it may be concluded that Ho is rejected. So there is a difference of husband?s knowledge about exclusive breastfeeding and their support among women who feed their babies with exclusive breastfeeding and those who do not. Suggestion from this research is to performed collaboration to design programs that can raise education about importance of exclusive breasfeeding to pregnant mother dan her family, particularly her husband. And for the next research to analized the other factors that related to exclusive breastfeeding supplies.